1986
DOI: 10.1029/jb091ib02p02137
|View full text |Cite
|
Sign up to set email alerts
|

Yield estimates of nevada test site explosions obtained from seismic Lg waves

Abstract: A methodology is presented for determining the yield of underground nuclear explosions from Lg wave amplitudes. The methodology is applied to Nevada Test Site (NTS) explosions, for which the data from short‐period, vertical component analog seismographs at three stations are used to develop calibration curves for unsaturated material and water‐saturated rock source conditions. The latter curves are found to provide reasonably accurate estimates of the yields of explosions in other areas of the United States an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
2
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(107 citation statements)
references
References 17 publications
6
98
2
1
Order By: Relevance
“…For example, it has been observed that Lg amplitude level correlates remarkably well with the known yields of underground explosions over broad source regions, and this fact seems difficult to reconcile with the Rg scattering hypothesis. Moreover, both of these proposed sources would predict a pronounced dependence of Lg excitation on source depth, and this seems inconsistent with the results of Nuttli (1986) and others who have obtained reliable Lg-based yield estimates for very deep explosions, including the U.S. Peaceful Nuclear Explosion (PNE) RULISON which was detonated at a scaled depth more than six times larger than the nominal Nevada Test Site (NTS) containment depth.…”
Section: Introductioncontrasting
confidence: 50%
“…For example, it has been observed that Lg amplitude level correlates remarkably well with the known yields of underground explosions over broad source regions, and this fact seems difficult to reconcile with the Rg scattering hypothesis. Moreover, both of these proposed sources would predict a pronounced dependence of Lg excitation on source depth, and this seems inconsistent with the results of Nuttli (1986) and others who have obtained reliable Lg-based yield estimates for very deep explosions, including the U.S. Peaceful Nuclear Explosion (PNE) RULISON which was detonated at a scaled depth more than six times larger than the nominal Nevada Test Site (NTS) containment depth.…”
Section: Introductioncontrasting
confidence: 50%
“…Also, 1 sec period Lg waves were used by Nuttli (1986) for estimating seismic magnitudes because their anelastic attenuation is small in shield and other geologically stable regions.…”
Section: The Methodsmentioning
confidence: 99%
“…where R is distance and y is the coefficient of anelastic attenuation, which, in its turn, is related to the quality factor, Q (Nuttli, 1986):…”
Section: Determination Of Low-frequency Spectral Levelmentioning
confidence: 99%